Integrando la conservación de la biodiversidad en la toma de decisiones a nivel local: un estudio de la disposición a pagar en el parque nacional Yanachaga-chemillen - Mogollón, Raymundo (2023)
Understanding the willingness to pay for biodiversity conservation improves the decision-making process for local governments in countries like Peru, characterized by ineffective development of public policies to protect the environment. During the first quarter of 2020, 2,414 surveys were conducted to measure the willingness to pay for biodiversity conservation in the Yanachaga-Chemillén National Park, in Peru. The results revealed that the willingness to pay is approximately $6 per household, which is relevant not only because it provides information on how the local population values this aspect but also because it has direct implications for the formulation and implementation of environmental conservation policies in the region.